Effect of Solution Treatment on Microstructure and Mechanical Properties of A356.2 Aluminum Alloy Treated With Al–Sr–La Master Alloy. Issue 6 (3rd April 2018) - Ding, Jian; Miao, Sainan; Ma, Baojun; Xia, Xingchuan; Qiu, Chuanrong; Chen, Xueguang
Abstract : Morphology and mechanical performances of A356.2 aluminum alloy under solution treatment are important for its application, specifically for alloys treated with newly‐developed combined refiner‐modifier. In this work, effect of solution temperature, solution time, and quenching medium temperature on the microstructure and mechanical properties of A356.2 aluminum alloy treated with Al–6Sr–7La master alloy are investigated. Results show that eutectic silicon undergo disintegration, spheroidization, and coarsening stages with solution temperature increasing. Volume fraction of eutectic silicon decreases gradually with solution temperature increasing from 495 to 550 °C, while secondary dendritic arm spacing (SDAS) increases gradually during this process. At the solution temperature of 540 °C, aspect ratio of eutectic silicon approached to about 1.3 and eutectic silicon undergo spheroidization and coarsening stages with extension of solution time. Moreover, SDAS increases with increasing of quenching medium temperature, which affects the ultimate tensile strength (UTS), yield strength (YS), and elongation (EL) of the alloy, especially for tensile strength and elongation. Optimal solution parameters for A356.2 aluminum alloy treated with Al–6Sr–7La are obtained and the reasons are discussed. Abstract : In this study, solution temperature, solution time, and quenching medium temperature are taken into account to improve microstructure and properties of as‐cast A356.2 aluminum alloy treated by Al–6Sr–7La. Microstructure observation and properties tests are used to select the optimal parameter in every step and the reasons are discussed.